PARTICIPATIVE DECISION-MAKING AND EMPLOYEE JOB SATISFACTION IN STARTUP ORGANIZATIONS: A STUDY OF ORGANIZATIONAL COMMUNICATION CLIMATE AT PRAKTIS.CO - Muhammad Ardhanie Amrullah; Agustisnus Rusdianto Berto; Endah Murwani (Universitas Muhammadiyah Jakarta, 2026)
Praktis.Co, as a startup company, has experienced increasing uncertainty due to a decline in organizational conditions, which has affected employee job satisfaction. This study aims to analyze the effect of dimensions of the organizational communication climate as variables on the job satisfaction of Praktis.Co employees. This study employs the concept of participative decision-making as a determinant of job satisfaction. A quantitative approach was used, applying a survey method targeting Praktis.Co employees who are on the lowest structural positions and first-level officials above the lowest. Data were collected through a cross-sectional questionnaire administered to 282 Praktis.Co employees, ranging from the lowest structural level to first-line officers. A total of 173 valid responses were obtained, exceeding the minimum sample size required based on the Slovin formula. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that participative decision-making has a significant effect on job satisfaction. Employees who are given opportunities to express opinions, provide feedback, and participate in organizational discussions tend to perceive themselves as valued members of the organization. Such involvement fosters a sense of ownership and psychological attachment to the organization. This study contributes to organizational communication literature by emphasizing participative decision-making as an independent and strategic dimension of communication climate influencing employee job satisfaction, particularly within startup companies experiencing organizational change and organizational uncertainty.